2018
DOI: 10.3233/jad-170436
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Alzheimer’s Disease: A Longitudinal Study in Norwegian Memory Clinics

Abstract: Abstract.Background: The course of Alzheimer's disease (AD) varies considerably between individuals. There is limited evidence on factors important for disease progression. Objective: The primary aim was to study the progression of AD, as measured by the Clinical Dementia Rating Scale Sum of Boxes (CDR-SB). Secondary aims were to investigate whether baseline characteristics are important for differences in progression, and to examine the correlation between progression assessed using three different instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 33 publications
6
50
0
3
Order By: Relevance
“…Our results agree, in part, with a recent longitudinal study from Norway by Eldholm et al (2018). 33 Similar to our finding that the majority of AD patients progresses relatively slowly, this study showed that approximately half of their sample consisted of slow progressors, defined as showing less than 1 point worsening in CDR-sb per year. As in our study, the slow progressors from the Norwegian cohort scored better on cognitive tests and the CDR-sb at diagnosis, as compared to the more rapid progressors.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results agree, in part, with a recent longitudinal study from Norway by Eldholm et al (2018). 33 Similar to our finding that the majority of AD patients progresses relatively slowly, this study showed that approximately half of their sample consisted of slow progressors, defined as showing less than 1 point worsening in CDR-sb per year. As in our study, the slow progressors from the Norwegian cohort scored better on cognitive tests and the CDR-sb at diagnosis, as compared to the more rapid progressors.…”
Section: Discussionsupporting
confidence: 87%
“…It should be noted that the study by Eldholm et al (2018) included only a single follow-up measurement after a mean follow-up time of 2 years, and its sample consisted of both AD and MCI patients. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, although TMEM106B variants do not associate with risk for developing the TDP-43 proteinopathy ALS, they do associate with cognitive impairment among individuals with manifest ALS. In this context, we point out that other genetic variants associated with increased risk for developing a disease have been associated with both faster progression of that disease (eg, APOE4 alleles in AD) 26 and slower progression (eg, LRRK2 G2019S in PD), 27 underlining the importance of formal evaluation in longitudinal studies. 3,25 We find here that TMEM106B variants that increase risk for FTLD-TDP may also associate with a faster rate of cognitive decline in clinically diagnosed FTD patients, with positive findings in the bvFTD subgroup as well.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the physical and cognitive tests were first performed at the baseline BL examination and could be sensitive to changes during this time period or due to the event of admission. However, the GMHR and CDR have shown to be stable over time [39][40][41]. Moreover, caregiver-reported data from the RUD questionnaire may have yielded inaccuracies in the extent of formal and informal care.…”
Section: Limitations and Strengthsmentioning
confidence: 99%